Korelasi antara Realistic Mathematic Education dan Self Regulated Learning Siswa dalam Pembelajaran Matematika - Rahmat Jumri; Risnanosanti Risnanosanti; Winda Ramadianti; Mardiah Syofiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The objective of this research is to determine whether Self-Regulated Learning and Realistic Mathematics Education Indonesia (PMRI) are related. A sort of research that is undertaken is library research, and the method used in this study is a qualitative descriptive one. The information was gathered from both domestic and foreign sources that have research, articles, or literature related to this activity. According to the findings of this research project, PMRI affects pupils' ability to self-regulate. Knowing this helps the teacher develop a variety of teaching techniques that will help him create self-reliant math pupils. In conclusion, imparting real-world mathematics (PMRI) to students has considerable benefits and may potentially be a key strategy for fostering motivation. Keywords: Mathematics, Realistic, Students, Learning